Differences in Dysfunction of Thenar and Hypothenar Motoneurons in Amyotrophic Lateral Sclerosis - Fang, Jia; Cui, Liying; Liu, Mingsheng; Guan, Yuzhou; Li, Xiaoguang; Li, Dawei; Cui, Bo; Shen, Dongchao; Ding, Qingyun (Frontiers in Human Neuroscience, 2016)
This study aimed to determine differences in spinal motoneuron dysfunction between the abductor pollicis brevis (APB) and the abductor digiti minimi (ADM) in amyotrophic lateral sclerosis (ALS) patients based on studying F-waves. Forty ALS patients and 20 normal controls underwent motor nerve conduction studies on both median and ulnar nerves, including F-waves elicited by 100 electrical stimuli. The F-wave persistence (P < 0.05), index repeating neuron (RN) (P < 0.001), and index repeater F-waves (Freps) (P < 0.001) significantly differed between the APB and the ADM in the normal control participants. For the hands of the ALS patients that lacked detectable wasting or weakness and exhibited either no or mild impairment of discrete finger movements, significantly reduced F-wave persistence (P < 0.001), increased index RN (P < 0.001), and increased index Freps (P < 0.001) were observed in APB in comparison with the normal participants, with relatively normal ADM F-wave parameters. For the hands of ALS patients that exhibited wasting and weakness, the mean F-wave amplitude (P < 0.05), the F/M amplitude ratio (P < 0.05), F-wave persistence (P < 0.001), index RN (P < 0.05), and index Freps (P < 0.05) significantly differed between APB and ADM. The differences in the dysfunction of motoneurons innervating APB and ADM are unique manifestations in ALS patients. The F-wave persistence (P = 0.002), index RN (P < 0.001), and index Freps (P < 0.001) in the APB seemed to differentiate ALS from the normal controls more robustly than the ADM/APB CMAP amplitude ratio. Thus, F-waves may reveal subclinical alterations in anterior horn cells, and may potentially help to distinguish ALS from mimic disorders.